Dispute Over Relief Package: Tax Cuts or Direct Transfers? - ZG Überblick (Wirtschaftsdienst)
Abstract Due to high inflation, the state benefits in various ways, for example due to the design of the progressive tax and transfer system in nominal terms. Some relief measures have already come into force. Various other measures have been announced. Finance Minister Christian Lindner has now made a proposal for tax relief that could be as high as 10 billion. However, this is a one-off ad hoc measure and not a fundamental reform. Is income tax reform necessary and is cold progression a problem that should be eliminated? Or are other reforms more urgent at the moment so that more socially balanced relief can be provided? Would a lump-sum transfer — as laid out in the coalition agreement — be more efficient and if so, what are the reasons for its failure? Which income groups should be particularly relieved in a reform?